Antimicosis activity of chloroform fraction of ethanol extract Soursop Leaves (Annona muricata, L.) - Elly Rustanti; Zenny Fatmawati (Department of D3 Medical Technology Laboratory STIKes Hutama Abdi Husada Tulungagung, 2019)
Fungal infections are often found in the community, some antifungal drugs have been less effective so it is necessary to look for new candidate drugs as antimycotic, one of the candidates is soursop leaf (Annona muricata, L.). Soursop leaves contain compounds alkaloids, polyphenols, flavonoids, triterpenoids that function as antifungals. The purpose of this study was to determine the antifungal activity of the n-hexane fraction of the Soursop ethanol extract of the fungus Candida albicans and determine the class of compounds that act as antimycotic. Soursop leaf was extracted by maceration method using ethanol 96% then fractionated by partition method using chloroform solvent. The chloroform fraction was tested for antifungal activity against the fungus Candida Albicans by diffusion method with a concentration variation of 10%, 20%, and 30%. then identified by UV-VIS and FTIR spectrophotometry to determine active compounds as antifungals. The results showed that the Soursop leaf chloroform fraction had the highest antifungal activity at a concentration of 30% with an inhibitory diameter of 25.4 mm which was categorized strong. Compounds that are suspected to have antifungal activity from the soursop leaf chloroform fraction are terpenoid compounds. The results of this study are expected to provide scientific information to the public about the benefits of soursop leaves as an alternative treatment for fungal infections caused by the fungus Candida Albicans.